Implantation of a leadless pacemaker as a promising solution for patients with arythmia – current state of knowledge - Maciąg, Anna; Branewska, Justyna; Olszanicka, Anna; Kołodziejczyk, Kacper; Ostrowska, Barbara; Hop, Izabela; Matysek, Mikołaj; Niemiec, Rafał; Galas, Adam; Imioło, Jan (Journal of Education, Health and Sport, 2023)
Introduction: In cardiac electrotherapy, new solutions are constantly sought to minimise the invasiveness of methods used so far and reduce the risk of complications. Implantation of traditional cardiac pacemakers carries risks of high probability that may cause both early and late adverse effects which are associated with presence of subcutaneous lodge and intravenous wires. A significant reduction in complications may be achieved by using leadless pacemakers the main representative of which is MicraTM (MicraTM transcatheter pacing system: TPS, Medtronic plc, Mounds View, MN, USA). Micra is 90% smaller than conventional pacemaker. The generator and electrode system is contained in one capsule-like device that is implanted directly into the right ventricle of the heart. The transcatheter pacing system is less invasive because it is placed in the heart with the use of a catheter via a femoral vein. thus no chest incision and scar. Purpose of the work: The aim is to present the subject of leadless cardiac pacing with the use of Micra device based on a review of current scientific publications. Methods and materials: The available medical literature related to cardiac pacing was analysed taking leadless technology into account. The analysed material was obtained from PubMed and Google Scholar. Conclusion: Cardiac electrotherapy with the use of leadless Micra pacemaker is a great example of substantial technological progress. Due to its structure and form, it is a beneficial alternative to a traditional pacemaker. It also offers promising solutions for the future. This is, however, a relatively new method of stimulation requiring further observation and analysis.